Implementation of fault tree analysis (FTA) in production process: A wood- based industry case study - Z.N.R., Aina; Sharizal, A.S.; Shuaib, Norshah Aizat; Hairi, Mohd Hendra; Radzif, T.M. (2023)
Fault Tree Analysis (FTA) is one of the tools used by various industries such as aerospace, oil and gas, automotive and other high-hazard risk industries to consider the rationale that leads to undesired condition or occurrence. It can also be used to reduce and maximize capital in the production process. This case study evaluates the issue by using the fault tree analysis (FTA) to increase the performance of the manufacturing cycle of a local business in Selangor, Malaysia. The approach helps to define the cause and impact of the product in the production process. The company has been searching for efficient ways to improve the productivity of its output. Potential causes and consequences have been identified during the study period. Based on the results, the company will consider finding strategies for managing input and output of production.